2019
DOI: 10.3390/ma12081315
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Fabrication of Ti-Ni-Si-O Nanostructures on Ti10Ni5Si Alloy

Abstract: Ti-Ni-Si-O nanostructures were synthesized on Ti10Ni5Si alloy through an electrochemical anodization in electrolyte solutions containing ammonium fluoride (NH4F). The anodic oxide structures were affected by the electrochemical anodization parameters, including the electrolyte viscosity, water content, anodization potential and anodization time. Using an anodization potential of 40 V for 90 min in an ethylene glycol/glycerol electrolyte with 3 vol.% deionized water, highly ordered self-organized nanotube array… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Figure 1a shows a SEM image of the homogenized alloy. Similar to the as-cast alloy reported in our previous work, the gray region, black region, and bright strip-like region were the α-Ti matrix, Ti 5 Si 3 phase, and Ti 2 Ni phase, respectively [34,35]. The XRD pattern of the alloy (Figure 1b) further proved the existence of the α-Ti and Ti 5 Si 3 phases [36].…”
Section: Resultssupporting
confidence: 83%
“…Figure 1a shows a SEM image of the homogenized alloy. Similar to the as-cast alloy reported in our previous work, the gray region, black region, and bright strip-like region were the α-Ti matrix, Ti 5 Si 3 phase, and Ti 2 Ni phase, respectively [34,35]. The XRD pattern of the alloy (Figure 1b) further proved the existence of the α-Ti and Ti 5 Si 3 phases [36].…”
Section: Resultssupporting
confidence: 83%
“…Morphology.-Ni/Si-doped TiO 2 nanostructures fabricated through electrochemical anodization of Ti-Ni-Si alloy have been discussed in our previous work. [31][32][33] It was found that vertically aligned self-organized nanotube arrays, regular nanopores, and etching pits grew at the α-Ti, Ti 5 Si 3 , and Ti 2 Ni phase region, respectively (Fig. 2a).…”
Section: Resultsmentioning
confidence: 99%
“…The implants have characteristics related to the materials with which they are made and to their geometry, macroscopic and microscopic. The material normally used is commercially pure titanium, this material has characteristics of biocompatibility, low density, electrochemical stability, high mechanical strength and sufficient rigidity [23,24,25,26,27,28,29]. The macroscopic implant geometries evaluate macroscopic differences in the shape of dental implants.…”
Section: Methodsmentioning
confidence: 99%